INCREASING ENVIRONMENTAL CARE STUDENTS THROUGH ECO-BRICKS AT SMP NEGERI 10 BANJARMASIN - Mawarni, Nurul; Hastuti, Karunia Puji; Angriani, Parida; Aristin, Nevy Farista; Muhaimin, Muhammad; Adyatma, Sidharta (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
SMP Negeri 10 Banjarmasin has seen a growing demand for the implementation of the Adiwiyata program, which is aimed at achieving environmental preservation through harmony, beauty, and comfort. Educators faced a challenge in raising students' awareness about environmental care, but a research study was conducted to address this through eco-brick activities. The study involved a closed questionnaire and the average score calculation resulted in 51.58, indicating that waste management through the Eco-brick program has a positive impact on reducing, reusing, and recycling attitudes among students. The results clearly demonstrate the effectiveness of the Eco-brick program in increasing students' awareness and understanding of the importance of maintaining environmental sustainability. It is evident that the Adiwiyata program is crucial for the future of our planet, and initiatives like eco-brick activities can certainly contribute to achieving this goal.